Evaluasi Penyuluhan Kesehatan terhadap Pengetahuan Taruna Remaja Tentang HIV/AIDS - Sukarman (Politeknik Penerbangan Makassar, 2019)
Where is in their growth they have common character among other like restlessness, opposition, imagination, group activity, and desire in trying everything, as a result teenager are not rarely trapped in promiscuity, free sex, drugs, etc. Giving health counseling intervention intended to obtain the description of Cadet Safety and enggenering academy Makassar third year student’s knowledge toward HIV/AIDS basic concept. This research aimed at finding out health counseling influence toward HIV/AIDS knowledge of Cadet Safety and enggenering academy Makassar third year students. This research represented quantitative with Pre-Experimental design, one group pre-test and post-test design. The population was Safety and enggenering academy Makassar third year students. The samples consisted of 165 respondents. The sampling technique was purposive sampling. Before intervention, Pre-test toward Cadet Safety and enggenering academy Makassar third year students done, the sampling technique next followed with giving counseling intervention about HIV/AIDS basic concept then evaluated by post-test. The data were collected through questionnaires with 22 questions based on Guttmann Scale scoring assessment. The data were analyzed through Repaired T-Test with significant level a = 5% (0, 05). The result of the data analysis with Repaired T-Test proved that there was health counseling influence toward HIV/AIDS knowledge of Cadet Safety and enggenering academy Makassar third year students, with the value of P=0,00 (a< 0,05).